PREPARATION OF 110K BI(PB)SRCACUO SUPERCONDUCTING THIN-FILMS BY RF MAGNETRON SPUTTERING AND THEIR RESPONSE TO MICROWAVE-RADIATION - Guldeste, A; Chern, J; Grovenor, C; Goringe, M; Dewhughes, D (1993)
Bi(Pb)SrCaCuO thin films containing a high ratio of Pb (Pb/Bi>1), about 0.5μm thick, were deposited on single crystal LaAlO3, SrTiO3 and MgO substrates by using a heavily Pb doped single composite oxide target. The film deposited on (001) MgO at a substrate temperature of 170°C and sintered at 852-862°C for 1 hour in air showed zero resistivity at 110K. The highest critical current density of 4.6×104 Amp/cm2 at 77K has been measured on the film grown on (100) LaAlO3. The dependence of the high-Tc (2223) and low-Tc (2212) phase concentrations on annealing temperature was also studied by X-ray diffraction. The highest fraction of the 2223 phase was obtained on the film annealed at 862°C for 1 hour. Microwave response measurements were carried out on a film patterned into a 150 μm wide and 1 cm long meander-type structure using standard photolithography and wet chemical etching. The result showed that the microwave response contains a non-bolometric component. © 1993.